Tackling for Human Trafficking: Village-based Movement of Migrant Workers in Lembata, Indonesia - Lindra Darnela; Ahmad Tholabi Kharlie (Jurnal Cita Hukum, 2023)
Studies on the role of villages in combating human trafficking have not been much discussed. This paper examines the efforts of the grass roots to counter human trafficking in Lembata, Indonesia. Data based on observations, interviews with the government, and discussions with six migrant workers' communities in Lembata. The methods used are qualitative research methods with literary approaches and empirical approaches. The results of the research indicate that the people of the village in Lembata have succeeded in providing alternative livelihoods for the former Indonesian Labour Force through the strengthening of the productive economy. This community has also been able to train and support the candidate TKI to acknowledge its rights and duties. This study proves that the bottom-up system is an effective way to tackle human trafficking.